Legal Review of Dualism in the Regulation of Release of Land Rights by Notaries and Sub-district Heads - Swastika, Rona (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Land ownership rights are legal rights or powers held by a person or an entity over a piece of land to use, control, and enjoy the land. It is determined for private parties or companies that wish to have land rights, the land ownership status that will be used for commercial development is required to experience degradation of rights, namely a decrease in land status that can be done in various ways, one of which is the release of rights followed by an application for new rights. A series of processes that must be taken to change the Land Ownership Certificate to Building Use Rights, the owner is required to have a Land Rights Release Statement Letter (SPPHT) or a Land Rights Release Deed to release the land status. It is stated in the Regulation of the Minister of Agrarian Affairs that the authority for the land rights release statement letter is two of them, namely the Notary and the Sub-district Head, each of whose authority is based on laws and government regulations. In examining the problem of this dualism of regulation, the author uses a normative research method with a legislative approach, a conceptual approach, and an analytical approach. Using secondary data sources from primary, secondary, and tertiary legal materials. The data collection method is carried out by literature study. The data analysis method uses a prescriptive method. The results of the study show that both officials, namely the Notary and the Sub-district Head appointed in the process of releasing land rights, both receive the authority in the form of attribution. However, the authority of the SPPHT according to the normative hierarchy is the authority of the Notary which cannot be replaced. In order to achieve legal objectives, the government grants the authority to issue one of them by the Sub-district Head. The existence of dualism brings benefits of convenience for people who live in areas not yet reached by Notaries, but there are also shortcomings, namely disharmony of regulations and inconsistencies in the mechanism for preparing documents. Both legal products in the form of a deed of release of rights made by a Notary and a statement of release made by the Sub-district Head both have legal force, are valid, and bind the parties.